IMPLEMENTATION OF THE AL-ADL CONCEPT IN THE PRACTICE OF MUZARA'AH AND MUKHABARAH IN THE DISTRICT'S LEADING AGRICULTURAL SECTOR BANTAENG SOUTH SULAWESI - Halim, Hasriliandi; Kara, Muslimin H.; Haddade, Abdul Wahid (Program Pascasarjana, UIN Alauddin Makassar, 2022)
The primary purpose of this research was to investigate the implementation of the al-Adl Concept on the Practices of Muzara'ah and Mukhabarah. This research particularly examined and determined the most suitable profit-sharing contract decisions to be applied to the leading agricultural sector in Bantaeng Regency. A qualitative research design was adopted in this study by using a phenomenological research approach. The data collection methods used in this study were observation, document analysis, and direct interviews with several informants. The data of this research were analyzed using descriptive qualitative data analysis and pairwise comparison scale qualitative analysis using the Analytical Hierarchy Process (AHP) method. The study results indicated that the community's practices of muzara'ah and mukhabarah in Bantaeng Regency had been well conducted.